(untitled) (Journal of Hama University, 2024)
The study was conducted on 76 pus samples taken from superficial abscesses in the head of sheep with the aim of isolating and identifying Corynebacterium pseudotuberculosis bacilli and determining the best antibiotics to treat them. The results of bacteriological tests showed the isolation of 15 isolates of Corynebacterium pseudotuberculosis from sheep in Hama Governorate. All samples underwent culture procedures on 1% Tellurite blood agar medium and were identified by studying their morphological, colouring, cultural and biochemical properties The results of the clinical examination of the infected sheep showed the presence of superficial abscesses in the suspected sheep in the head and neck area, with a percentage of 93.4%, respectively. Abscesses were not observed in the loin and buttock area. The results of culture and isolation showed that 15 isolates of C. pseudotuberculosis were isolated, with a rate of 19.3%. By conducting antibiotic sensitivity test of C. pseudotuberculosis isolates on Mueller Hinton Blood agar culture, it was found that they are sensitive to Tylosin, Ampicillin, Enrofloxacin, Erythromycin and Doxycycline. They were resistant to Penicillin and Kanamycin. C. pseudotuberculosis can be identified by conventional methods in bacterial diagnostic laboratories, and the use of other methods such as molecular methods may be more reliable, and this requires further research in this field.